Transcriptional Autoregulation by BRCA1 - de Siervi, Adriana (2010)
The BRCA1 gene product plays numerous roles in regulating genome integrity. Its role in assembling supermolecular complexes in response to DNA damage has been extensively studied; however, much less is understood about its role as a transcriptional coregulator. Loss or mutation is associated with hereditary breast and ovarian cancers, whereas altered expression occurs frequently in sporadic forms of breast cancer, suggesting that the control of BRCA1 transcription might be important to tumorigenesis. Here, we provide evidence of a striking linkage between the roles for BRCA1 as a transcriptional coregulator with control of its expression via an autoregulatory transcriptional loop. BRCA1 assembles with complexes containing E2F-1 and RB to form a repressive multicomponent transcriptional complex that inhibits BRCA1 promoter transcription. This complex is disrupted by genotoxic stress, resulting in the displacement of BRCA1 protein from the BRCA1 promoter and subsequent upregulation of BRCA1 transcription. Cells depleted of BRCA1 respond by upregulating BRCA1 transcripts, whereas cells overexpressing BRCA1 respond by downregulating BRCA1 transcripts. Tandem chromatin immmunoprecipitation studies show that BRCA1 is regulated by a dynamic coregulatory complex containing BRCA1, E2F1, and Rb at the BRCA1 promoter that is disrupted by DNA-damaging agents to increase its transcription. These results define a novel transcriptional mechanism of autoregulated homeostasis of BRCA1 that selectively titrates its levels to maintain genome integrity in response to genotoxic insult.